Combined pancreatic and gastric heterotopia in small intestine presenting as intussusception-A rare congenital anomaly - Tejasvita Singh; Sonal Tripathi; Shatakshee Tewari; Kachnar Varma; Vatsala Misra (Wolters Kluwer Medknow Publications, 2021)
Pancreatic and gastric heterotopias are rare congenital anomalies which have been reported throughout the length of the gastrointestinal tract. Combined gastric and pancreatic heterotopias, although very rare, have been described mainly in the duodenum followed by jejunum with ileum being a rare site. The reported incidence of this combined heterotopias is low, ranging from <1% to 13%. Extensive literature search has revealed that only Four cases of combined pancreatic and gastric heterotopias have been reported in the small intestine till date. Hence, we report this case for its rarity and unusual presentation as intussusception in a young male.